2015
DOI: 10.1115/1.4029565
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Microgrooved Cutting Tool in Dry Machining of AISI 1045 Steel

Abstract: This paper studies the performance of microgrooved cutting tool in dry orthogonal machining of mild steel (AISI 1045 steel) using advantedge finite element simulation. Microgrooves are designed on the rake face of cemented carbide (WC/Co) cutting inserts. The purpose is to examine the effect of microgroove textured tools on machining performance and to compare it with nontextured cutting tools. Specifically, the following groove parameters are examined: groove width, groove depth, and edge distance (the distan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(13 citation statements)
references
References 23 publications
0
13
0
Order By: Relevance
“…A optimal edge distance may reduce cutting force, tool wear and stress. The good choice of edge distance may be taken as edge radius [32]. In the present study, the dimple was created from edge of cutting tool of 50 µm.…”
Section: Chip Flow Angle and Chip Curlingmentioning
confidence: 99%
“…A optimal edge distance may reduce cutting force, tool wear and stress. The good choice of edge distance may be taken as edge radius [32]. In the present study, the dimple was created from edge of cutting tool of 50 µm.…”
Section: Chip Flow Angle and Chip Curlingmentioning
confidence: 99%
“…However, to the best of our knowledge, the combined application of soft and hard coatings to dry cutting has not yet been reported. To obtain the best combination of soft and hard coatings from known materials, three-factor five-level (L 25 5 6 ) orthogonal experiments were designed. The three factors were the coating thickness, coating material, and thickness ratio of soft and hard coatings, and the five levels of each factor are described in detail in Table 2.…”
Section: Orthogonal Experiments Designmentioning
confidence: 99%
“…However, the cutting fluid application increases not only the processing costs but also the environmental pollution risks [3,4]. Therefore, green processing technology (without cutting fluids) is a sustainable development trend, which has become increasingly topical [5,6]. However, dry cutting exposes the tool to more heavy-duty conditions because of the inevitably increased cutting forces, cutting temperatures, and tool wear [7].…”
Section: Introductionmentioning
confidence: 99%
“…Ma et al carried out a series of simulative studies in tools with grooves texture [96,97], holes texture [98] and bumps texture [99]. In these studies, dimensional and locational parameters were considered, as shown in Table 5.…”
Section: Fem Simulationmentioning
confidence: 99%